The Role of Individual Values, Authoritarian Attitudes and Social Identity in the General Discriminatory Orientation of the Personal in Russia - Shamionov, R.M. (Socialʹnaâ Psihologiâ i Obŝestvo, 2020)
Objective. Study of the role of individual values, authoritarian attitudes and social identity in the expression of discriminatory orientation of the personal in Russia. Background. Discriminatory attitudes not only hinder social development, but also negatively affect interpersonal and intergroup relationships, creating social and humanitarian problems. Therefore, finding out and explaining the reasons for the formation of a discriminatory attitude and determining how to eliminate them are the most important tasks of modern social psychology. Study design. The paper studied the relationship between the degree of dislike for representatives of various discriminated groups and the areas of discrimination by calculating the Pearson correlation. Predictors of discriminatory attitudes are established using regression analysis (step-by-step method). Structural modeling of the determinants of discriminatory attitudes of the individual by area (sphere) of discrimination and subject (discriminated group) using the SEM method is carried out. Participants. The study involved 217 people (the average age is 28.9±11.2 years, 36% of men). Measurements. We used the developed questionnaire and scales of discriminatory attitudes, the method of assessing values of Sh. Schwartz, a short version of the scales of the method of J. Dukkit. All scales are checked for meaningful validity and reliability. Results. It was found that the discriminatory attitude is most pronounced in the sphere of sports, education and career. Biases and rejection of representatives of different groups in various spheres of life are associated with the high significance of the values of personal and social security, power — resources, traditions (positive); values of interpersonal conformity and independence — thoughts (negative) and reputation as a desire to maintain a public image (ambivalent in different areas). The directions of relations between values, authoritarian attitudes, social identity and discriminatory attitudes are established. Сonclusions. It is shown that civil identity is a factor of institutional discrimination rather than domestic one. Adherence to an ethnic group affects the strength of a domestic discriminatory attitude directly, and institutional attitudes indirectly, through civic identity. As a result of structural equation modeling, a suitable model has been determined that explains up to 24% of variations in the outgroup discriminatory attitude and up to 25% of variations in the manifestation of biases in various spheres of life. Цель исследования. Изучение роли индивидуальных ценностей, авторитарных установок и социальной идентичности в выраженности дискриминационной направленности личности в России. Контекст и актуальность исследования. Дискриминационные установки не только тормозят общественное развитие, но и самым негативным образом отражаются на межличностных и межгрупповых взаимоотношениях, создавая социальные и гуманитарные проблемы. Поэтому выяснение и объяснение причин формирования дискриминационной установки и определение способов их устранения являются важнейшими задачами современной социальной психологии. Дизайн исследования. В работе изучались взаимосвязи между степенью неприязни к представителям различных дискриминируемых групп и сферами дискриминации через подсчет корреляции Пирсона. Установлены предикторы дискриминационной установки с использованием регрессионного анализа (пошаговый метод). Проведено структурное моделирование детерминант дискриминационных установок личности по области (сфере) дискриминации и предмету (дискриминируемой группе) методом SEM. Выборка. В исследовании приняли участие 217 человек (средний возраст составляет 28,9±11,2 лет, 36% мужчин). Методы. Использованы разработанные анкета и шкалы дискриминационных установок, методика оценки ценностей Ш. Шварца, короткая версия шкал методики Дж. Даккита. Все шкалы проверены на содержательную валидность и надежность. Результаты. Установлено, что дискриминационная установка наиболее выражена в сфере спорта, образования и карьеры. Предубеждения и неприятие представителей разных групп в различных сферах жизнедеятельности связаны с высокой значимостью ценностей безопасности личностной и общественной, власти — ресурсов, традиций (положительно); ценностей конформизма межличностного и самостоятельности — мысли (отрицательно) и репутации как стремления поддержать публичный имидж (амбивалентно в разных сферах). Установлены направления связей между ценностями, авторитарными установками, социальной идентичностью и дискриминационными установками. Основные выводы. Показано, что гражданская идентичность выступает скорее фактором институциональной дискриминации, нежели бытовой. Приверженность к этнической группе влияет на силу бытовой дискриминационной установки прямо, а институциональной — опосредованно, через гражданскую идентичность. В результате моделирования структурными уравнениями определена подходящая модель, объясняющая до 24% вариаций аутгрупповой дискриминационной установки и до 25% вариаций проявления предубеждений в различных сферах жизнедеятельности.